2020
DOI: 10.1093/cercor/bhaa362
|View full text |Cite
|
Sign up to set email alerts
|

Neural Basis of Semantically Dependent and Independent Cross-Modal Boosts on the Attentional Blink

Abstract: The present study recorded event-related potentials (ERPs) in a visual object-recognition task under the attentional blink paradigm to explore the temporal dynamics of the cross-modal boost on attentional blink and whether this auditory benefit would be modulated by semantic congruency between T2 and the simultaneous sound. Behaviorally, the present study showed that not only a semantically congruent but also a semantically incongruent sound improved T2 discrimination during the attentional blink interval, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
45
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(68 citation statements)
references
References 96 publications
17
45
6
Order By: Relevance
“…Furthermore, the neural generators of unisensoryevoked N400 effects have been localized mainly to the middle/ superior temporal cortex (Khateb et al, 2007;Khateb, Pegna, Landis, Mouthon, & Annoni, 2010;Lau, Phillips, & Poeppel, 2008), which is also a well-documented brain region of multisensory integration (Beauchamp, 2005;Calvert, 2001). The statistical analysis yielded that the present cross-modal N440 component was elicited significantly only when a semantically incongruent sound synchronized with T2, in accordance with the recent finding that this component was sensitive only to audiovisual stimuli with semantic conflict (Zhao et al, 2021).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Furthermore, the neural generators of unisensoryevoked N400 effects have been localized mainly to the middle/ superior temporal cortex (Khateb et al, 2007;Khateb, Pegna, Landis, Mouthon, & Annoni, 2010;Lau, Phillips, & Poeppel, 2008), which is also a well-documented brain region of multisensory integration (Beauchamp, 2005;Calvert, 2001). The statistical analysis yielded that the present cross-modal N440 component was elicited significantly only when a semantically incongruent sound synchronized with T2, in accordance with the recent finding that this component was sensitive only to audiovisual stimuli with semantic conflict (Zhao et al, 2021).…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, the current study showed that the occipitally distributed early cross-modal ERP component (i.e., P195) was positive in polarity, whereas this component was found to be negative (i.e., N195) in the recent study conducted by Zhao et al (2021).…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…This finding contradicts the assumption of a generally larger effect of visual compared to auditory distractors on the detection of a target in the same modality. That the cross-modal distractor effect appears to be reduced compared to the unimodal visual effect might be attributed to an enhancement of visual target processing by a concurrent auditory cue, which has been demonstrated for other paradigms (Frassinetti et al, 2002;Noesselt et al, 2008;Noesselt et al, 2010;Van der Burg et al, 2011;Zhao et al, 2020). This multisensory enhancement might counteract the distractor-induced inhibition to a certain degree.…”
Section: Discussionmentioning
confidence: 63%